Auditory processing and non-auditory factors associated with hyperacusis in children with auditory processing disorder (APD). (1st January 2021) - Ahmmed, Ansar Uddin; Mukherjee, Dipankar
Abstract: Purpose: Prevalence of hyperacusis in children presenting with listening difficulties (LiD) or developmental auditory processing disorder (APD) is uncertain. The relationships between hyperacusis, auditory profiles and non-auditory factors are unclear, information which is important in understanding and managing APD and hyperacusis. Method: A retrospective study of 282 children with APD (165 males and 117 females) aged 6–16 years. Hyperacusis was ascertained by parental response to question about 'oversensitivity to sounds'. Auditory and non-auditory features including anxiety, attention deficit hyperactivity disorder and oppositional defiant symptoms, language profile and non-verbal ability (NVIQ) were compared between those with and without hyperacusis. Results: Of the 282 children 200 (70.9%) had hyperacusis. There were no significant differences in age, NVIQ and auditory processing profiles between the two groups ( p > .05). In addition to poor speech perception in noise 79% of children performed poorly mainly in temporal processing and/or dichotic listening tests. The hyperacusis group had significantly more anxiety, hyperactivity/impulsivity, oppositional defiant symptoms and pragmatic language impairment when analyzed separately. However, only anxiety and language impairment were significant in binary logistic regression analyses. Conclusions: The prevalence of hyperacusis is high in APD, but auditory processing profiles were similar in those with and without hyperacusis. The high prevalence of anxiety, externalising behaviour, pragmatic language impairment in those with hyperacusis noted in APD is similar to those reported in children with autism spectrum disorder and Williams syndrome. However, when shared variances are addressed only anxiety and language impairment predicted hyperacusis. Holistic auditory processing assessment is suggested in hyperacusis.